A função administrativa e a proteção constitucional do direito de moradia - Cedano, Sérgio (2010)
The administrative function is eminently teleological, since it is related to satisfying primary interests, and as such, finds itself supported by two basic principles: the supremacy of public interest over the private and the inalienability of public interests. In order to be valid, all administrative actions must follow the human being s principle of dignity, whether in its negative sense, aiming at stopping the State s arbitrary actions, or in its positive perspective, in which the State must have as permanent objective the protection of life in all its connotations. In the exercise of the administrative function, the State realizes activities such as intervention on social domain, by means of public policies and activities to support the administration, the management of public assets and the power of the police. The state inaction is considered illegitimate and an illegal practice, in such a way as providing individuals who had their rights violated the right to make demands on the State. The Federal Constitution, paragraph 9 or article 23, defined as common administrative competence of the Union, the States, Federal District and Municipalities, the promotion of programs to build homes and to improve the living conditions and basic sanitation. Therefore, it is observed that the issue of having a residence is inserted in the context of the right-power of the State, included in the scope of the minimum vital space or existential minimum for the execution of the subjective right of a dignified life (art. 6, CF). The Constitutional Text, establishing expressly that property must have its social function (art. 5, 23) and, especially when it is considered everyone s existence with dignity as a principle of the economic order, according to the social justice (art. 170, 2 e 3), resulted in the emergence of a new internal structure of the concept of property. The inclusion of the social function principle modifies the structure of the right of ownership, in that to own leaves the condition of a mere observer of erga omnes respect, as a mere universal passive subject, and starts to consider subjective rights, following the superior constitutional consideration of the social right of residence and the consequent access to minimum vital assets, including in the relation with the State